MENAKAR MUTU PELAYANAN DI ERA PANDEMI COVID-19:: ( Studi pada JakEvo ) - Muchamad Chazienul Ulum; Sherina Ayu Setyawati (Jurnal Administrasi Publik, 2023)
Measuring Service Quality in the Covid-19 Pandemic Era: Study on JakEvo. The implementation of public services in Indonesia is still facing problems related to maladministration practices related to licensing, especially during the Covid-19 pandemic. Since 2018 the implementation of licensing services in DKI Jakarta has gone through Jakarta Evolution (JakEvo) as an electronic licensing service system. One of the sub-district technical implementing units that uses JakEvo is the Investment Management Unit and One-Stop Integrated Service in Cilandak. However, in practice there are still problems with refusal of permits which are always increasing and have an impact on unstable service ratings. JakEvo should have facilitated licensing services during the Covid-19 pandemic. The purpose of this study is to determine service quality which can be viewed from the dimensions of security, communication, reliability, responsiveness, and delivery. The type of research used is descriptive with a qualitative approach. The results of the study show that the quality of licensing services through JakEvo during the Covid-19 pandemic has gone quite well in a five-dimensional perspective. However, there are things that need to be improved on the reliability dimension related to truth and accuracy to clarify in providing information related to service standard operating procedures (SOP).